PENDAMPINGAN PASTORAL BAGI ANAK JALANAN - Frieska Putrima Tadung; Elsye Esterina Londo (Institut Agama Kristen Negeri Manado, 2022)
Basically, street children are a group of children who face a lot of problems. Street children are children who are forced into existence by a situation (economic factors, harmony, family, criminality, and so on) that he himself does not want so as to make himself have to maintain his existence as an adult human to continue living by working anything, anywhere, and anytime they can. One of the factors that cause the emergence of street children is economic problems or parents encouraging children to work for reasons to help the family economy, etc. This researcher saw the need for a pastoral counseling service in providing assistance to street children. This study used descriptive qualitative that seeks to describe a social symptom. Pastoral care is a solid foundation for the understanding of pastoral counseling. Pastoral care is a dimension of the church that needs to be done considering that throughout the span of life, the people will not be separated from unexpected crises or problems. Assistance or accompanying is an activity that can help the conseli.